PENGARUH PEMBERIAN AROMATERAPI CYMBOPOGON CITRATUS DALAM MENINGKATKAN APPETITE PADA ANAK - Adelia Despriyanti; Silvia Mona; Abdi Dharma (Universitas Batam, 2024)
Nutritional problems in toddlers in Indonesia are still high, with a significant prevalence of stunting. Poor appetite in children aged 2 to 6 years is a major factor affecting their nutritional status. One proposed non-invasive solution is aromatherapy with Cymbopogon Citratus (lemongrass), which is known to be calming, stimulating the digestive system, and increasing appetite through stimulation of the olfactory nerve. A quantitative approach was used, involving the participation of children from PAUD Kinta Anak Ceria. This study used a quasi-experimental method with a one-group pretest-posttest design without a control group. Before the administration of aromatherapy, a pretest was conducted to measure the level of children's appetite. After the intervention with Cymbopogon citratus aromatherapy, a posttest was conducted to assess the changes that occurred. This study revealed the effect of Cymbopogon Citratus aromatherapy on the appetite of children at PAUD Kinta Anak Ceria. With a quantitative Quasi-Experiment design, 20 children were observed before and after the administration of aromatherapy for two weeks. The results showed a significant increase in appetite, from an average of 46.00 to 80.25 with a P-Value of 0.000. In conclusion, Cymbopogon Citratus aromatherapy is effective in increasing children's appetite and is recommended to be applied more widely, involving families and educational institutions, and supported by health workers to ensure its safe and effective use.